Malignancies in the Parotid Glands: A Histopathological Analysis - Mahesh Kumar Luhano, Fareeha Naseer Syed, Afia Sarwar, Urwa Sarwar, Sabah Kaleem Baloch, Fnu Anjali, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to examine the incidence of benign and malignant parotid tumors, as well as their age and gender distributions, and histomorphological characteristics. Study Design: Retrospective study Place and Duration: Liaquat University of Medical and Health Sciences, Jamshoro in the duration from July, 2022 to December, 2022. Methods: The department of pathology examined a total of 47 Parotid tumor specimens. Sections were obtained, processed, and paraffin-embedded after specimens were formalin-fixed. Slides were prepared, hematoxylin and eosin was used to stain them, and then the paraffin blocks were sliced. (WHO) histological type was used to categorize the cancers. The gathered data were statistically examined. Results: There were majority 26 (55.3%) males and 21 (44.7%) females in this study. Among all, 34 (72.3%) cases had benign tumor and 13 (27.7%) cases were had malignant tumor. Among 34 cases of benign tumor, pleomorphic adenoma was the most common found in 17 cases and in malignant tumor mucoepidermoid carcinoma was the most common found in 6 cases. Majority of the cases of benign tumor were aged between 30-50 years. Conclusion: Parotid tumors are significant even though they are uncommon because they exhibit a great variety of morphologic variability between various tumor types and occasionally even within a single tumor mass. Hence, a precise diagnosis is crucial and may be made by a histological study. Keywords: Histopathological Examination, Parotid Tumors, Mucoepidermoid Carcinoma, Pleomorphic Adenoma